(untitled) (Biological Sciences - PJSIR, 1998)
A series of ESR experiments were carried out at atmospheric as well as low pressures in order to find any relation- ship between paramagnetic species and the charge carriers in pyrrole based electrically conducting polymers. ESR spectra recorded for a range of polymer sampleshavingelectrical conductivities spreadover four orders of magnitude suggest that apparently there is no link between the paramagnetic centres and bipolarons which serve as the major charge carriers in these materials. A series of ESR measurements at low temperatures for pyrrole based polymers showthat mostofthepolymers obeyCurie-Weisslawintermsofincreaseinspinpopulations.Differenceinbehaviour of various polymers in terms of changes in spin populations, line shape and line width is attributed to the difference in molecular structure and morphology.